Analisa Faktor Yang Mempengaruhi Organizational Citizenship Behavior Karyawan PT.Bank Sumut Kantor Pusat Medan - Amriansyah, Muhammad D; Tahura, Tengku Lyza; Hafas, Hafriz Rifki (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This study aims to analyze the significant influence of organizational climate, employee engagement, work palcement and organizational commitment on the organizational citizenship behavior of PT.CentralSumatera Bank Medan. The totalpopulation in this studyamounted to 531 employee and use 84 employee as a sample. The analysis technique used is multiple regression analysis. The results showed that organizational climate, work placement and organizational commitment had a significant effect on organizational citizenship behavior andemployee engagement had a not significant effect on organizational citizenship behavior at PT. Central Sumatera Bank Medan. As simultan effect the organizational climate, employee engagement, work placement and organizational commitment had a significant effect on organizational citizenship behavior at PT. Central Sumatera Bank.